2017
DOI: 10.15547/ast.2017.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and serum biochemical indices of broiler chickens fed raw sickle pod (Senna obtusifolia) seed meal

Abstract: Editors and Sections Genetics and Breeding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
2
1
Order By: Relevance
“…The body weight of the pigs fed the control diet 0.13kg was less than those fed the experimental diets which were almost similar(P˃0.05) statistically. This was in agreement with the report of Augustine et al (2017) for Senna obtusifolia seeds. Adjoudji et al (2005).…”
Section: Growth Performance Of Weaner Pigs Fed Sickle Pod Leaf Mealsupporting
confidence: 94%
See 1 more Smart Citation
“…The body weight of the pigs fed the control diet 0.13kg was less than those fed the experimental diets which were almost similar(P˃0.05) statistically. This was in agreement with the report of Augustine et al (2017) for Senna obtusifolia seeds. Adjoudji et al (2005).…”
Section: Growth Performance Of Weaner Pigs Fed Sickle Pod Leaf Mealsupporting
confidence: 94%
“…The proximate composition of Senna obtusifolia leaves are presented in Table 2. Showed that, the dry matter obtained in this study is (92.32%) and is higher than the values (90.50%) reported by Augustine et al, 2017 and Adjoudji et al, (2005) and (18.46%) reported by Ismaila et al (2011). However, lower than (27.40%) reported by Ayssiwede et al (2012).…”
Section: Proximate Composition Of Senna Obtusifolia Leaf Mealcontrasting
confidence: 68%
“…(2016) found that fermentation was most efficient in reducing the ANFs content and improving the protein content and quality of the seed. Feeding the raw seed meal up to 250 g/kg did not affect hematological parameters in broilers but even as low as 50 g/kg increased serum aspartate amino transferase ( AST ), alanine transferase ( ALT ), alkaline phosphatase ( ALP ) compared to the control group ( Augustine et al., 2017b ). An important function of the liver is the conversion of toxic substances into forms readily excreted.…”
Section: Effects Of Senna Seed Meal On Poultry Performancementioning
confidence: 99%
“…(2017) 50 g/kg – broilers Depressed growth, feed: gain and nutrient digestibility. Augustine et al. (2017b) 75 g/kg Depressed weight gain, feed intake and feed: gain.…”
Section: Effects Of Senna Seed Meal On Poultry Performancementioning
confidence: 99%